2021
DOI: 10.1590/1678-5150-pvb-6655
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of B-mode ultrasonography for detecting malignancy in canine cutaneous neoplasms: preliminary results

Abstract: The aim of this study was to verify the applicability and accuracy of B-mode ultrasonography in detecting malignancy in dog cutaneous neoplasms. Forty-two neoplasms (12 benign and 30 malignant) of mesenchymal, round cells, epithelial and melanocytic origins from 24 dogs of different breeds and ages were included. The ultrasound evaluation was performed with a linear multi-frequency transducer (7.0 to 12MHz), with frequency dependent on the mass dimension. Ultrasonographic characteristics of echogenicity (hypo/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…The heterogeneous echotexture indicative of malignancy seen in cutaneous and subcutaneous tumors is explained by the different structural components, such as the presence of cavitary areas, points of fibrosis, or microcalcifications. The association between heterogeneous echotexture and malignancy was already demonstrated in previous studies with different types of neoplasms (cutaneous and mammary) in both humans and animals [ 13 , 15 17 , 20 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The heterogeneous echotexture indicative of malignancy seen in cutaneous and subcutaneous tumors is explained by the different structural components, such as the presence of cavitary areas, points of fibrosis, or microcalcifications. The association between heterogeneous echotexture and malignancy was already demonstrated in previous studies with different types of neoplasms (cutaneous and mammary) in both humans and animals [ 13 , 15 17 , 20 ].…”
Section: Discussionsupporting
confidence: 54%
“…There were no associations with echogenicity, which may be related to the different pathological processes involved, such as active inflammation or tissue necrosis in different tumor types [ 19 ]. A preliminary study involving 42 cutaneous neoplasms showed an association between malignancy and hypoechogenicity [ 15 ]. A greater number of neoplasms and specific types of skin cancer that were included in the present study may explain the discrepancy between the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of ARFI elastography has grown exponentially in recent years in medicine and veterinary medicine, so that this diagnostic modality can be used, in humans, as a predictor of malignancy in lymph node lesions 15 , 27 , in thyroid 28 and splenomegaly 29 , 30 . Through this technique, it was already possible to verify that, in cases of breast cancer in bitches, metastatic lymph nodes had a higher shear wave velocity than healthy lymph nodes 31 , which is a promising technique in veterinary oncology.…”
Section: Discussionmentioning
confidence: 99%
“…As for cutaneous and subcutaneous canine neoplasms, a few studies have demonstrated the applicability of ultrasonographic methods on tumor diagnosis and differentiation. A preliminary study found that predominantly hypoechoic, heterogeneous neoplasms with signs of invasiveness in adjacent tissues were more prone to malignancy [15]. On Doppler, it has been veri ed that cutaneous mast cell tumors have lower resistivity indices than soft tissues sarcomas and benign lesions [16].…”
Section: Introductionmentioning
confidence: 99%